The Autophagy Related Gene CHAF1B Is a Relevant Prognostic and Diagnostic Biomarker in Hepatocellular Carcinoma - Zhang, Zunni; Zhang, Yalong; Mo, Wuning (Frontiers in Oncology, 2021)
The role of autophagy in tumors is complex; based on known interactions between autophagy and hepatocellular carcinoma (HCC) pathogenesis, we hypothesized that autophagy-related genes (ARGs) may play an important role in HCC. The ARGs were obtained from the Human Autophagy Database and the Gene Set Enrichment Analysis. Based on the area under the curve (AUC) value > 0.9 with p < 0.0001 and Student’s T-test analysis with p < 0.0001, differently expressed autophagy-related genes (DEARGs) with high diagnostic efficiency were found. Besides that, we searched in the PubMed database to find novel DEARGs associated with HCC. Then the DEARGs were validated in the GSE25097, GSE54236, GSE76427, GSE64041, Oncomine, and Human Protein Atlas datasets. Finally, survival analysis of CHAF1B in HCC, and correlations of clinico-pathological characteristics and CHAF1B were performed based on TCGA database. The mRNA and protein expression of 531 ARGs were analyzed and validated in eight independent cohorts. First, 18 DEARGs with high diagnostic efficiency were selected from the TCGA database, and 9 of them were identified that had not previously been associated with HCC. These 9 DEARGs were validated in the GSE25097, GSE54236, GSE76427, GSE64041, Oncomine, and Human Protein Atlas datasets. Additionally, we found that CHAF1B was associated with overall survival and relapse free survival at one, three, and five years. Furthermore, the univariate and multivariate Cox analyses revealed that the high expression of CHAF1B was an independent risk factor in HCC patients. This research demonstrated that CHAF1B was a novel diagnostic and prognostic signature biomarker that could be potentially useful for predicting the development of HCC and may provide new insights for HCC tumorigenesis and treatments.